Innate Lymphoid Cells in Inflammatory Bowel Disease - Xin Yao; Kaiming Ma; Yangzhuangzhuang Zhu; Siyan Cao (Cells)
Inflammatory bowel disease (IBD), including Crohn’s disease and ulcerative colitis, is a chronic inflammatory disorder of the gastrointestinal tract with rising incidence and an unclear etiology. Innate lymphoid cells (ILCs) have recently emerged as key regulators of mucosal immunity and tissue homeostasis and are increasingly implicated in IBD. Unlike adaptive lymphocytes, ILCs do not require antigen recognition and clonal expansion to respond rapidly to environmental cues and shape immune responses. In a healthy gut, ILCs maintain intestinal homeostasis by guarding the epithelial barrier, protecting against pathogens, and mounting proper responses to external insults. However, their altered differentiation, proliferation, recruitment, activation, and interaction with other host cells, microbiota, and environmental stimuli may contribute to IBD. In this review, we discuss recent advances in understanding murine and human ILCs in the context of intestinal inflammation and IBD. A deeper understanding of ILC-mediated immune mechanisms may offer novel therapeutic strategies for restoring intestinal homeostasis and improving personalized management of IBD.